24‐Hour Kinetics of Cardiac Troponin‐T Using a "High‐Sensitivity" Assay in Thoroughbred Chuckwagon Racing Geldings after Race and Associated Clinical Sampling Guidelines. (24th November 2017) - Shields, E.; Seiden‐Long, I.; Massie, S.; Leguillette, R.
Abstract : Background: A "high‐sensitivity" cardiac troponin‐T (hscTnT) assay recently has been validated for use in horses and is a specific biomarker of myocardial damage. Postexercise release kinetics of cTnT utilizing the hscTnT assay have yet to be established in horses. Objectives: To determine: (1) cTnT release kinetics in racing Thoroughbreds after a high‐intensity 5/8th mile Chuckwagon race; (2) the effects of age on pre‐ and postrace cTnT concentrations; and (3) sampling guidelines for clinicians evaluating horses presenting after exercise. Animals: Samples were obtained from 38 Thoroughbred geldings aged 5–16 years before racing and immediately, 2, 3, 4, 6, 12, and 24 hour postrace. Methods: Prospective, observational study with convenience sampling. A fifth‐generation hscTnT assay was used for plasma sample analysis, and concentrations were compared at all time‐points. Correlations were determined between cTnT concentrations and age. Biochemistry analysis was performed to assess rhabdomyolysis, renal failure, and exercise‐induced dehydration. Results: All horses with measureable cTnT concentrations had significant postexercise increases in cTnT with a median peak (8.0 ng/L) at 3‐hour postrace. All horses had peak postexercise cTnT concentrations 2‐ to 6‐hour postrace ≤ the 99th percentile upper reference limit of 23.2 ng/L, after which all cTnT concentrations decreased until returning to baseline by 12–24 hours. There was no correlation over time between cTnT concentrations and age. Conclusions and Clinical Importance: In racing Thoroughbreds completing short‐duration, high‐intensity Chuckwagon races, cTnT concentrations are expected to be increased 2‐ to 6‐hour postrace and to decrease by 12–24 hours while remaining ≤23.2 ng/L throughout. This study contributes to establishing guidelines for clinical use of the hscTnT assay in exercising horses.